(untitled) (Nóema, 2022)
In philosophy we find public and politically meanigful moments and other ones that are essentially individual. Is there something as a boundary between these two dimensions? Is it somehow detectable? What are the limits of the presence of the social influence in the individual mind? I make reference in this writing to the works of Piaget, Nietzsche, Foucault, Elias. The main conceptual tools that I use are connected with the function of experience and of induction.